2004
DOI: 10.4049/jimmunol.173.6.4147
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nitric Oxide Synthase 2 Expression by Distamycin A Improves Survival from Endotoxemia

Abstract: NO synthase 2 (NOS2) plays an important role in endotoxemia through overproduction of NO. Distamycin A (Dist A) belongs to a class of drugs termed minor-groove DNA binders, which can inhibit transcription factor binding to AT-rich regions of DNA. We and others have previously shown that AT-rich regions of DNA surrounding transcription factor binding sites in the NOS2 promoter are critical for NOS2 induction by inflammatory stimuli in vitro. Therefore, we hypothesized that Dist A would attenuate NOS2 up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…Cells were then lysed in 100 ul reporter lysis buffer (Promega, Madison, WI) and the luciferase activity in 50 ul of aliquots of cell lysates was measured using Luciferase Assay System (Promega, Madison, WI) according to the manufacturer's protocol. To monitor the transfection efficiency, a beta-galactosidase assay was conducted using the same lysate according to the published protocol[34]. All constructs were sequenced before transfection and each experiment was independently repeated four times with triplicate wells for each transfection reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were then lysed in 100 ul reporter lysis buffer (Promega, Madison, WI) and the luciferase activity in 50 ul of aliquots of cell lysates was measured using Luciferase Assay System (Promega, Madison, WI) according to the manufacturer's protocol. To monitor the transfection efficiency, a beta-galactosidase assay was conducted using the same lysate according to the published protocol[34]. All constructs were sequenced before transfection and each experiment was independently repeated four times with triplicate wells for each transfection reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The functions of nicotinamide in numerous enzymatic reactions and its relatively low toxicity in vivo have suggested that it might act as a pharmacological agent with potential effects on different pathologies, such as cancer, diabetes and infectious disease [33, 34]. Nicotinamide has been thought to be a potential therapeutic agent in the fields of medicine and nutrition; however, whether nicotinamide works together with other vitamins, such as RA or D3, and its function in cellular processes such as ERK activation involved in cell differentiation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages express high levels of iNOS and are important sources of iNOS-derived nitric-oxide (NO), which together with the respiratory burst of reactive oxygen species (ROS), leads to effective bactericidal activity [2,6]. NO has a paradoxical role in severe sepsis, where it has a harmful effect by contributing to lung injury in animals and humans [7,8], and a beneficial effect on immune system and in lungs through antimicrobial activity [911]. Recently it has been reported that monocyte/macrophage-derived iNOS plays a pivotal role in mediating resolution of lung injury by modulating lung immune responses, thus facilitating clearance of alveolar inflammation and promoting lung repair [12].…”
Section: Introductionmentioning
confidence: 99%